PENGARUH SELF-EFFICACY TERHADAP HASIL BELAJAR KEWIRAUSAHAAN SISWA SMK REKAYASA DENPASAR - Anggreni, Ni Luh Putu Yesy; I Putu Eka Indrawan; Ni Komang Sri Yuliastini (Program Studi Pendidikan Ekonomi Universitas PGRI Mahadewa Indonesia, 2025)
The purpose of this study was to determine the significant effect of self-efficacy on the entrepreneurial learning outcomes of students at SMK Rekayasa Denpasar. The hypothesis proposed in this study is that there is a significant effect of self-efficacy on the entrepreneurial learning outcomes of students at SMK Rekayasa Denpasar. Based on the results of the analysis of the second hypothesis test, the t-count value was 3.459> t table = 2.14 and had a significance of 0.004 <0.05. It can be concluded that the Self Efficacy variable has a significant effect on the Student Learning Outcomes variable in the Entrepreneurship Subject of Class XI SMK Rekayasa Denpasar in the 2024/2025 Academic Year.